Penilaian Kualitas Gas SF6 Pada GISTET 500/150 kV - Rahman Azis Prasojo; Devi Soviati Mahmudah; Imron Ridzki; Muhammad Fahmi Hakim; Priya Surya Harijanto (Elposys: Jurnal Sistem Kelistrikan, 2022)
The number of Gas Insulated Switchgear (GIS) in operation is increasing in Indonesia. GIS failure requires expensive costs andextensive blackouts. Asset reliability management such as SF6 is needed to ensure GIS performance. Several studies have tested thequality of SF6 gas to assess the feasibility and operation of the GIS. However, a complete GIS feasibility study based on SF6 gas qualityparameters has not found. In this study, a condition assessment of the GISTET Kembangan 500/150 kV was carried out based on applicableinternational standards. There is an interesting phenomenon in the form of dew point anomaly and moisture content in severalcompartments, indicating that the gas is moist. The results of this study indicate the operational feasibility of the GISTET Kembangan500/150 kV , the effect of high humidity on GIS operations, and maintenance recommendations.